Determination of Cytotoxicity Properties of Newly Synthesized Chalcone-Cyclophosphazene Compounds against Human Prostate Cancer Cell Lines - Tekin, Suat; Koran, Kenan; Ozen, Furkan; Sandal, Suleyman; Gorgulu, Ahmet Orhan (Wiley, 2015)
[Abstract Not Available]